Effect of Growth Performance and Survival Rate of Goldfish (Carassius auratus L. 1758) Fed Garlic (Allium sativum L.) Supplemented Diets - Balci, BA; Aktop, Y; Arslan, MN; Ünver, AÇ; Özbas, M; Kilic, H (Journal of the Hellenic Veterinary Medical Society, 2024)
This research evaluated the effect of different garlic (Allium sativum) levels on the nutritional characteristics, growth, and survival rate of goldfish (Carassius auratus). Five different commercial experimental diets were prepared garlic was added at levels of 0 (Control), 5, 10, 15, and 20 g·kg-1. The experiment was carried out for 84 days. Diet 4 group, in which 20 g·kg-1 garlic was added to the trial feed, showed the best growth performance compared to Diet 0 (Control) and other groups (Diet 1, Diet 2, Diet 3) (p<0.05). The best growth in parameters such as body weight gain, percent live weight increase, and specific growth rate was in the Diet 4 group (p<0.05). It was determined that the statistical difference between the groups for the condition factor and survival rate parameters was insignificant. The highest feed conversion rate was determined in the Diet 0 group with the lowest Diet 4 group (p<0.05). As a result, it has been determined that feeding goldfish with the addition of garlic up to 20 g·kg-1 (2%) in its diet will have a positive effect on growth.